2016
DOI: 10.1128/jvi.02395-15
|View full text |Cite
|
Sign up to set email alerts
|

3C Protease of Enterovirus D68 Inhibits Cellular Defense Mediated by Interferon Regulatory Factor 7

Abstract: Human enterovirus 68 (EV-D68) is a member of the EV-D species, which belongs to the EV genus of the Picornaviridae family.Over the past several years, clusters of EV-D68 infections have occurred worldwide. A recent outbreak in the United States is the largest one associated with severe respiratory illness and neurological complication. Although clinical symptoms are recognized, the virus remains poorly understood. Here we report that EV-D68 inhibits innate antiviral immunity by downregulation of interferon reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 57 publications
1
60
0
Order By: Relevance
“…6D) expression was also not affected by CV-A16 3C pro . It was reported previously that the EV-A71 and EV-D68 3C pro proteins induce the cleavage of IRF7 (37,39). We did not detect a cleaved IRF7 product in the presence of CV-A16 3C pro (Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…6D) expression was also not affected by CV-A16 3C pro . It was reported previously that the EV-A71 and EV-D68 3C pro proteins induce the cleavage of IRF7 (37,39). We did not detect a cleaved IRF7 product in the presence of CV-A16 3C pro (Fig.…”
Section: Resultssupporting
confidence: 54%
“…Increasing evidence suggests that EV-A71 3C pro targets innate immune factors, such as RIG-I, TRIF, IRF7/9, the TAK1/TAB1/TAB2/TAB3 complex, and NLRP3, to modulate type I IFN and cytokine responses (34)(35)(36)(37)(38). Recently, EV-D68 3C pro has been reported to target IRF7 and TRIF to disable innate sensing responses (39,40). However, little is known about the function of the CV-A16 and CV-A6 3C pro proteins in innate immunity.…”
mentioning
confidence: 99%
“…During enterovirus infection, several signaling molecules in the RLR pathway have been suggested to be cleaved by 2A pro (MDA5 and MAVS) and 3C pro (RIG-I, MAVS, IRF7, and IRF9) (21,23,26,27,29,44,45). There are conflicting observations, and the question remained of which, if any, of the identified cleavages is important for inhibiting IFN-␣/␤ gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Both viral proteases, 2A pro and 3C pro , cleave various factors of the RLR signaling pathway, implicating them in the suppression of IFN-␣/␤ gene transcription. Overexpression of 3C pro of several enteroviruses has been shown to result in the cleavage of MAVS, IRF7, and IRF9 and, as a consequence, in the suppression of a coexpressed IFN reporter construct (24)(25)(26)(27)(28). However, in several of these studies, convincing evidence that the cleavage products observed upon 3C pro overexpression are the same as those observed in enterovirus-infected cells is lacking.…”
mentioning
confidence: 99%
“…IRF7 stimulates type‐I IFN production, such as IFNα, thereby activating the JAK‐STAT pathway in adjacent cells . The 3C pro of EV‐A71 can process IRF7 at a cleavage site between Gln189 and Ser190 in vitro and in vivo , while the 3C pro of EV‐D68 does so at two sites (Gln167↓Ala168 and Gln180↓S190) .…”
Section: Rna‐virus Proteases Interfering With the Host Innate Immune mentioning
confidence: 99%